STUDI KOMPARASI PELAYANAN KESEHATAN PESERTA JKN DAN UMUM TERHADAP KEPUASAN PASIEN DALAM PERSPEKTIF ISLAM (STUDI PUSKESMAS PAMIJAHAN KABUPATEN BOGOR) - Siti Silpi Salpiah; Ujang Buchori Muslim; Bayu Purnama Putra (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
This research is motivated by the prevalence of news about the quality of health services which is considered less satisfactory and tends to be low on BPJS patients compared to general patients. This research is quantitative with a comparative approach, namely to find out whether there are similarities or differences between one object and another and the data collection methods are using questionnaires and interviews. The method of collecting questionnaire data was carried out on respondents with sampling using the Non Probability Sampling technique, with the sampling method using incidental samples, while determining the number of samples according to Roscoe in the book Research Methods For Business. The interviews were conducted with puskesmas staff in order to complete the data in this study. And the data processing method in this study uses the Chi-Square method. The results showed that there were differences in the service quality of BPJS patients and general patients on patient satisfaction. This is based on the results of the analysis of the chi-square calculation, it can be seen that Asymp.Sig 0.000 ˂ 0.05, then reject H0 and accept H1. In general, Pamijahan community health services are measured from the service variables that are in accordance with the Islamic concept of QS. Ali Imran: 159.